Answers

2015-08-04T19:11:52+05:30
Let the two numbers be x and y, with x being the bigger number and y being the smaller number.
hence, according to first condition, x-y=3.
»y=x-3...(I)
The difference of their squares is 51.
Hence, x²-y²=51...(II)
now, substituting the value of y in equation (II), we get,
x²-(x-3)²=51
x²-x²+6x-9=51
6x=60...(+x² and -x² cut and 51 + 9)
x=60/6
x=10
Now, substituting the value of x in equation (I),
y=10-3
y=7
Therefore, values of x and y are 10 and 7 respectively.
Hence, 10 and 7 are the two numbers.

0